ENHANCEMENT INSTITUTIONAL CAPACITY OF CAMPUS ENTREPRENEURSHIP THROUGH BUSINESS COMMUNITY DEVELOPMENT IN SOME COLLEGES IN INDONESIA - Puspitasari, Devy M.; Adiyanti, Siska Ayudia; Setiadi, Nugroho J. (Universitas Brawijaya, Indonesia, 2018)
This study aims to determine the factors that affect entrepreneurship capital among students at several universities in Indonesia. The focus of this research is to identify the determinants of entrepreneurial attitudes and intentions. Specifically, this study investigates the views of respondents regarding entrepreneurship in terms of enhancing the institutional capacity of campus entrepreneurship. It further examines the respondents through self-assessment on entrepreneurship quality and their views on entrepreneurs. In addition, the importance of the various benefits and values for starting a business and the role of influencers according to their perceptions of entrepreneurship will also be analyzed. This study was analyzed through descriptive research method with the aim of obtaining profiling in terms of certain demographic attributes. Thus, entrepreneurship attitudes and intentions can build entrepreneurship skills through appropriate learning methods supported by strengthening the institutional capacity of campus entrepreneurship as a business incubator, container assistance, and entrepreneurship training.